Patagonotothen tessellata - Hüne, M. (2020)
This demersal species inhabits nearshore rocky reefs and kelp forests in southern Chile and Argentina and has an estimated generation length of 5 years. The global-level center of its abundance is in the straits of southern Chile. Invasive Chinook salmon now occur throughout the straits of Chile, and this represents a potential major threat, including impacts from competition, predation and disease introduction. The invasion is expected to expand into other parts of its range (i.e. Argentina). The Chilean salmon aquaculture industry, which is the source of escaped individuals, is expected to expand in the near future. The centre, or the major proportion of its global population is concentrated in the area where this threat is greatest. This threat has been increasing over time, but probably began about 30 years ago. There are no data to quantify population trends at this time; and considering this major threat and the lack of understanding for the likely direct impact, it is listed as Data Deficient. It is highly recommended to conduct studies on population trends as well as the impacts from the invasive salmon. Recommended conservation actions include the continued protection of kelp forests from harvest and to improve management of invasive salmon and prevention of escapes.